Bedankbrief van Ed Polak, gedateerd 29-6-1960, voor de belangstelling getoond voor zijn 80e verjaardag op 14-6-1960
Bedankbrief van Ed Polak, gedateerd 29-6-1960, voor de belangstelling getoond voor zijn 80e verjaardag op 14-6-1960.